A Universal Method for Achieving Ultra‐Low Contact Resistances in Organic Electrochemical Transistors - Luis‐Abraham Lozano‐Hernández; Patrice Rannou; Yvan Bonnassieux; Sébastien Sanaur (Advanced Materials Interfaces)
Abstract Organic ElectroChemical Transistors (OECTs) are intensively studied for enabling their use in organic bioelectronics, neuromorphic systems, and biosensors. Beyond device geometry, reaching optimal operation of organic electronic circuits requires the optimization of the physico‐chemical properties of the channel. Toward this end, the effects of a “bulk” doping of the channel material and its influence on the contact resistance (RC) at the interface between a Polymeric Mixed Ionic‐Electronic conductors (PMIECs) and the Source (S) and Drain (D) electrodes are presented. An easy‐to‐implement method to achieve ultra‐low contact resistances in OECTs is introduced. By incorporation of LiTFSI, a 4x transconductance improvement is achieved, and a decrease of RC by a factor of ≈2 and ≈40 has been observed for p‐type or n‐type PMIECs, respectively. It reaches an unprecedented width‐normalized contact resistance value as low as 1 Ohm.cm with the p(g2T‐T) polymer. The formation of very localized domains in the polymeric matrix in the vicinity of the electrodes, as a result of the reduction of TFSIˉ anions, which modulates the energy barrier at the S/D interface, is suggested here. Furthermore, both p(g2T‐T) and p(gNDI‐gT2) polymers exhibit low water uptake with minute amounts of LiTFSI. Worth noticing, doped p(g2T‐T) preserves its volumetric capacitance and demonstrates an exceptional long‐term stability. Finally, a universal strategy to fine‐tune OECT performances, drawing prospects for implementing next‐generation applications in organic bioelectronics and neuromorphics, is proposed.